2015
DOI: 10.12688/f1000research.5654.2
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of mRNA splicing mutations in genetic disease: review of the literature and guidelines for information-theoretical analysis

Abstract: The interpretation of genomic variants has become one of the paramount challenges in the post-genome sequencing era. In this review we summarize nearly 20 years of research on the applications of information theory (IT) to interpret coding and non-coding mutations that alter mRNA splicing in rare and common diseases. We compile and summarize the spectrum of published variants analyzed by IT, to provide a broad perspective of the distribution of deleterious natural and cryptic splice site variants detected, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 245 publications
1
41
0
1
Order By: Relevance
“…mRNA, and thus favored the missplicing. Branch site mutations are known to cause missplicing (Caminsky et al, ; Maslen, Babcock, Raghunath, & Steinmann, ). In this case, only Hexplorer indicated increased ESE scores in the new exon (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…mRNA, and thus favored the missplicing. Branch site mutations are known to cause missplicing (Caminsky et al, ; Maslen, Babcock, Raghunath, & Steinmann, ). In this case, only Hexplorer indicated increased ESE scores in the new exon (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms are also possible. For instance, we (De Boer et al, ) and others (Caminsky, Mucaki, & Rogan, , in a review) have found mutations that create or activate a “stronger” splice site than the wild‐type (w.t.) splice site, resulting in an incorporation of incomplete or extended exons.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The effect of the splicing mutation c.1177‐2A>G was predicted using the Splicing Mutation Calculator (Caminsky et al. ) (http://splicemc.cytognomix.com/). New splice site prediction was performed using the Berkeley Drosophila Genome Project (BDGP) (Reese et al.…”
Section: Methodsmentioning
confidence: 99%